L'homophobie - Borrillo, Daniel; Mécary, Caroline (Que sais-je?, 2019)
« L'homophobie est l'attitude d'hostilité à l'égard des homosexuels, hommes ou femmes. Quelles sont ses origines ? Quels sont ses rapports avec les autres formes de stigmatisation et de discrimination ? Comment, et à partir de quels discours, la suprématie hétérosexuelle, ainsi que la dévalorisation corrélative de l'homosexualité, ont-elles été construites ? Existe-t-il une personnalité homophobe? Et par quels moyens peut-on lutter contre cette forme de violence ? »-- Quatrième de couverture.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; droit; histoire et politique; homophobie; hétérosexisme; premier cycle; science politique et droit; soc2014; systèmes d'oppressions; thématiques; violences

Crip theory and the disabled identity: why disability politics needs impairment - Jenks, Andrew (Disability & Society, 2019)
This article highlights the importance of recognizing both the ontology of impairment as it relates to the creation of the disabled identity as well as why articulations of the disabled identity being ‘crip’ obfuscate potential politics. Examining how the disabled identity has been cast as a coherent social and political category, rather than the messy and complicated identity it truly is, I argue the adoption of a post-structuralist orientation by activists and advocates is bad for disability politics. Providing two examples, the first focusing on a publicized rape case of a person with an intellectual disability and the second on the importance of disability rights claims based on visibility of impairment, I show how articulations like those made in crip theory can have serious, negative implications for the lived experience of people with disabilities. I conclude with a call for disability studies scholars to engage disability politics in their work.
Keywords: 2000 à aujourd'hui; 2010-2019; activisme; approches et analyses; capacitisme; care; corps; cours; crip; discipline; droit; droit des personnes en situation de handicap; histoire et politique; justice sociale; postmodernisme; premier cycle; périodes historiques; ressource en ligne; santé; science politique; science politique et droit; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap